Use of Supraclavicular Flap by End to Side Technique in Pharyngeal SCC: A Case Report and Review of Literature - Ahmadi, Aslan; Sanaei, Ayda; Jan, Delaram; Zolfaghary, Maryam (Case Reports in Otolaryngology, 2021)
Objectives. In recent years, conservation laryngeal surgeries, including partial pharyngectomy, have been introduced as an alternative procedure for selected cases of hypopharyngeal squamous cell carcinoma (HSCC). Reconstruction of these defects presents a considerable challenge for the surgeon after partial pharyngectomy due to its circumferential nature. In this case report, we represent the innovative “End to side” technique to reconstruct hypopharyngeal defect using the rolled supraclavicular flap after laryngeal-preserving partial pharyngectomy. Methods and Results. A 70-year-old female presented with a history of progressive dysphagia and odynophagia. The evaluations revealed a T3N0M0 SCC of pyriform sinus. The mass was successfully resected through partial pharyngectomy, and the hypopharyngeal defect reconstruction was achieved using the rolled supraclavicular flap via the “End to side” technique. The patient was discharged after decannulation on day 10. The 3-week barium swallow was performed with no evidence of anastomotic leakage, and the oral feeding was started after NG tube removal. At week 5, complete movement of the true vocal cord on the one side and good phonation and deglutition was observed. There was no evidence of recurrence after 1 year. Conclusions. Laryngeal-preserving partial pharyngectomy and hypopharyngeal reconstruction with the rolled supraclavicular flap via the “End to side” technique could lead to good oncological and functional outcomes in selected cases of pyriform sinus.